Flufenamic acid reduces alveolar bone loss and pyrazole 3 enhances alveolar bone recovery in periodontitis mice - Kim, Ae Ri; Kim, Aeryun; Yang, Yu-Mi; Yoo, Yun-Jung; Bak, Eun-Jung (Journal of veterinary science (Suwŏn-si, Korea), 2025)
Transient receptor potential canonical 6 (TRPC6) and TRPC3 are involved in bone remodeling and other biological processes. To investigate the effects of TRPC6 activator, flufenamic acid (FFA), and TRPC3 inhibitor, pyrazole 3 (PYR), in human periodontal ligament (hPDL) cells and periodontitis mice. The effects of FFA and PYR on osteoblastogenesis were evaluated in hPDL cells. To investigate periodontitis induction, mice were randomized to control (C), periodontitis (P), and FFA-treated periodontitis (P+FFA) groups. To investigate periodontitis recovery, mice were randomized to day 0 C (D0C), D0P, D3P, D3P+PYR, D7P, and D7P+PYR groups. Alveolar bone (AB) area, osteoclast formation, osteoid area, and Runt-related transcription factor 2 (RUNX2) and receptor activator of nuclear factor-κB ligand (RANKL) expression were evaluated. AB area was greater in the P+FFA group than in the P group, whereas the number of osteoclasts and RANKL expression were lower. AB and osteoid areas were larger in the D7P+PYR group than in the D7P group. RUNX2-positive osteoblasts were elevated in the D3P+PYR group compared to the D0C and D0P groups. Osteocalcin expression was significantly greater on D28 of osteoblast differentiation in hPDL cells in the PYR group compared to the differentiation group. These results suggest that FFA attenuates AB loss by inhibiting RANKL expression and osteoclast formation and that PYR contributes to AB recovery by enhancing new bone formation.